ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN (Persepsi Konsumen Hotel Golden Tulip Tangerang) - Pandji Pratopo (JURNAL LENTERA BISNIS, 2021)
Hotels are an element of the tourism industry and play a very important role in providing services to tourists. Each hotel tries to improve its facilities and service quality. If consumers enjoy services that are much lower than they expected, consumers will lose interest in these service providers, and the hotel will eventually lose customers. Conversely, if consumers enjoy services higher than their expectations, then consumers will feel satisfied. Based on the research background, the questions that arise in this study are which factors have the most influence on customer satisfaction on the service quality of the Golden Tulip Hotel Tangerang, and what factors have the greatest influence on customer service expectations of the Golden Tulip Hotel Tangerang. The research model developed in this study consists of four dimensions, namely service quality, consumer expectations, and customer satisfaction, with two hypotheses to be tested. The test was carried out using the Structural Equation Modeling (SEM) analysis tool in the LISREL program on 100 respondents who were consumers of the Golden Tulip Hotel Tangerang. The results of data analysis indicate that the two proposed hypotheses are acceptable, and it can be concluded that service quality has a positive effect on customer satisfaction, and consumer expectations have a positive effect on customer satisfaction. This study also links the research results with the theoretical implications and policies of the Golden Tulip Hotel Tangerang management, which are described in the conclusion section. Research limitations and future research agendas can be used as a reference for future researchers.Keywords: service quality, customer expectations, customer satisfaction